Comparison of Lipstick Preparation Formulations of Red Dragon Fruit Extract (Hylocereus polyrhizus) and Aloe vera Extract (Aloe vera L.) as a Lip Colorant and Moisturizer with Lipstick Preparations Without Extracts - Athaya Wijdan Pascadiksa; Fitra Kamila Rahma; Elvina Widyasari Amarylis; Verna Wimala Salsabila; Dzikrina Adibah Salma (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Lipstick is a type of cosmetic widely used to beautify the appearance of the lips. Excessive use of artificial colors can cause irritation, so safer natural ingredients are needed. Red dragon fruit peel (Hylocereus polyrhizus) contains natural dyes betacyanin which has the potential as a natural dye and antioxidant, while Aloe vera acts as a natural moisturizer. This study aims to explore the potential of red dragon fruit peel extract and Aloe vera in making lipstick and assess its physical quality and antioxidant activity. The research methodology includes dragon fruit peel extraction using maceration techniques and Aloe vera extraction using infundation methods, which are then formulated into lipstick with cera alba, carnauba wax, cetyl alcohol, and vaseline album as the base ingredients. Product evaluation includes organoleptic tests, pH, homogeneity, spreadability, hardness, irritation, melting point, weight uniformity, cyclic stability testing, and antioxidant activity using the DPPH method. The results showed that the lipstick formula using the extract produced a bright red color, a pH of 5, was stable at extreme temperatures, non-irritating, and had an antioxidant activity of 1.13 mgQE/g. It is hoped that this research can provide an alternative for the development of natural-based cosmetics that are safe, environmentally friendly, and provide antioxidant and moisturizing benefits to the lips.